Efektywna demokracja parlamentarna Michela Debré - Ujazdowski, Kazimierz M. (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In the 1930s, France epitomized a weakness of parliamentary democracy. Third Republic, that was recognized by many European countries as a model political system, was actually hit by a grave crisis combined with an increase of popularity of authoritarian trends. Undoubtedly, ineffectiveness of the French model of parliamentary democracy contributed to the fall of republican France in 1940. An in-depth and interesting analysis, which may also be recognized as an attempt made to overcome the weaknesses of parliamentary democracy, was put forward by Michel Debré in his writings published in the WWII years. One of the reasons why his draft of a rationalized parliamentary system deserves special attention is that this document inspired establishment of the Fifth Republic. Debré offered an exceptional lesson of critical thinking about the political system. This outstanding lawyer was able to correctly identify and effectively eliminate the vices of parliamentary governments.
Keywords: autorytaryzm; Debré, Michel; skuteczna demokracja; reforma konstytucyjna; Piąta Republika we Francji; zracjonalizowany system parlamentarny